Investigating the biology of relapsed acute leukemia: Proceedings of the Therapeutic Advances for Childhood Leukemia & Lymphoma (TACL) Consortium Biology Working Group. (3rd October 2017) - Bhojwani, Deepa; Burke, Michael J.; Horton, Terzah; Ziegler, David S.; Sulis, Maria Luisa; Schultz, Kirk R.; Wayne, Alan; Izraeli, Shai; Chang, Bill H.
ABSTRACT: During the 2016 Therapeutic Advances for Childhood Leukemia & Lymphoma (TACL) Consortium investigators' meeting (Los Angeles, CA), a Biology Working Group was established to support the consortium's mission of developing innovative therapies for currently incurable childhood leukemias and lymphomas. The charge of the Biology Working Group was to address how TACL could advance biological investigations of pediatric relapsed/refractory hematologic malignancies while undertaking forward-looking therapeutic trials. To this end, the TACL Biology Committee was established to provide the scientific platform needed to further develop preclinical and translational studies that will advance the understanding and treatment of relapsed and refractory disease. The Biology Committee will focus on ensuring state-of-the-art studies that address biological components of early phase clinical trials, and developing a central biology bank of materials from these early phase trials for interrogations into the mechanisms of disease resistance.